Intracranial Arterial Dolichoectasia - Del Brutto, Victor J.; Ortiz, Jorge G.; Biller, José (Frontiers in Neurology, 2017)
Abstract An increased diameter (ectasis) and/or long and tortuous course (dolichosis) of at least one cerebral artery define intracranial arterial dolichoectasia (IADE). IADE could be detected incidentally or may give rise to an array of neurological complications including ischemic stroke, intracranial hemorrhage, or compression of surrounding neural structures. The basilar artery is preferentially affected and has been studied in more detail, mainly due to the presence of accepted diagnostic criteria proposed by Smoker and colleagues in 1986. Criteria for the diagnoses of dolichoectasia in other cerebral arteries have been suggested. However, they lack validation across studies. The prevalence of IADE is approximately 0.08–6.5% in the general population, while in patients with stroke, the prevalence ranges from 3% and 17%. Variations among case series depend on the characteristics of the studied population, diagnostic tests used, and diagnostic criteria applied. In rare instances, an underlying hereditary condition, connective tissue disorder, or infection predispose to the development of IADE. However, most cases are sporadic and associated with traditional vascular risk factors including advanced age, male gender, and arterial hypertension. The link between this dilative arteriopathy and other vascular abnormalities such as abdominal aortic aneurysm, coronary artery ectasia and cerebral small vessel disease suggest and underlying diffuse vascular process. Further understanding is needed on the physiopathology of IADE and how to prevent its progression and clinical complications.